Interrelationship Between Contractility, Protein Synthesis and Metabolism in Mantle of Juvenile Cuttlefish (Sepia officinalis) - Lamarre, Simon G.; MacCormack, Tyson J.; Bourloutski, Émilie; Callaghan, Neal I.; Pinto, Vanessa D.; Andrade, José P.; Sykes, Antonio V.; Driedzic, William R. (Frontiers in Physiology, 2019)
Young juvenile cuttlefish (Sepia officinalis) can grow at rates as high as 20% body weight per day. How the metabolic demands of such a massive growth rate impacts muscle performance that competes for ATP is unknown. Here we integrate aspects of contractility, protein synthesis, and energy metabolism in mantle of specimens weighing 1.1 g to lend insight into the processes. Isolated mantle muscle preparations were electrically stimulated and isometric force development monitored. Preparations were forced to contract at 3Hz for 30 sec to simulate a jetting event. We then measured oxygen consumption, glucose uptake and protein synthesis in the hour following the stimulation. Protein synthesis was inhibited with cycloheximide and glycolysis was inhibited with iodoacetic acid in a subset of samples. Under basal conditions, inhibition of protein synthesis impaired contractility and decreased oxygen consumption. An intact protein synthesis is required to maintain contractility possibly due to rapidly turning over proteins. 41% of whole animal ṀO2 is used to support protein synthesis in mantle, while the cost of protein synthesis (50 µmol O2 mg protein-1) in mantle was in the range reported for other aquatic ectotherms. A single jetting challenge stimulated protein synthesis by approximately 25% (2.51 to 3.12 % day-1) over a 1 h post contractile period, a similar response to that which occurs in mammalian skeletal muscle. Aerobic metabolism was not supported by either extracellular glucose or on-board glycogen, leading to the contention that at this life stage amino acids are catabolized. An intact glycolysis is required to support contractile performance and protein synthesis under basal conditions but apparently not because of a major contribution to energy production. It is proposed that glycolysis is needed to maintain intracellular ionic gradients. Intracellular glucose at approximately 3 mmol L-1 was higher than the 1 mmol L-1 glucose in the bathing medium suggesting an active glucose transport mechanism. Glycolysis was not activated and octopine did not accumulate during a single physiologically relevant jetting challenge; however, octopine accumulation increased following a stress that is sufficient to lower Arg-P and increase free arginine.